Impact of Psychological Factors on Early vs. Late-Onset Psoriasis: A Comparative Analysis - Elif Afacan Yıldırım; Muhterem Polat (Dermatology Practical & Conceptual, 2025)
Introduction: Psoriasis is a chronic inflammatory disease that significantly impacts psychosocial well-being. This study compares clinical and psychosocial characteristics between early-onset (<40 years) and late-onset (≥40 years) psoriasis patients.